Ag@WO3 core–shell nanocomposite for wide range photo detection - Jehan A. Saimon; Evan T. Salim; Mustafa Hadi Amin; Makram A. Fakhri; Ahmad S. Azzahrani; Ali B. M. Ali; Subash C. B. Gopinath (Scientific Reports, 2024)
Abstract This study successfully synthesized high-performance photodetectors based on Ag-WO3 core–shell heterostructures using a simple and economical two-step pulsed laser ablation in water method and has investigated the electrical characteristics of the Ag@WO3 nanocomposite heterojunction. The Hall effect tests indicate that the synthesized Ag@WO3 exhibits n-type conduction with a Hall mobility of 1.25 × 103 cm2V-1S-1. Dark current–voltage properties indicated that the created heterojunctions displayed rectification capabilities, with the highest rectification factor of around 1.71 seen at a 5 V bias. A photodetector’s responsivity reveals the existence of two response peaks, which are situated in the ultraviolet and visible region. The photodetector demonstrates a rapid response time of less than 100 ms. The detectivity values for wavelengths of 350 nm and 490 nm were 35 × 1013 Jones and 28 × 1013 Jones, respectively. The n-Ag-WO3/n-Si photodetector achieved a maximum EQE of 11.5% in the ultraviolet wavelength when subjected to 3 V and illuminated with 350 nm (26 mW/cm2) light. The devices demonstrate rapid switching behavior with a rise time of 0.32 s and a fall time of 0.33 s. The time-dependent light response of a photodetector under illumination at 26 mW/cm2 is seen at a bias of 3 V. The light exhibits a rise and decay duration of 15 s, while the photocurrent gain is measured at 9µA. The photocurrent of devices exhibited a positive correlation with the incoming light intensity, suggesting that the junction has the potential to function as a photo detector.